Meloxicam Decreases the Formation of Peritoneal Adhesions in an Experimental Surgical Model in Rats - Luis Alfredo Hernandez Villarroel; Henry Fernandez; Luisa Cesin (University Library System, University of Pittsburgh, 2017)
Background: Inflammatory adhesions result from an inflammatory response of the peritoneum during an intra-abdominal inflammatory process secondary to thermal or mechanical injury, infection, radiation, ischemia, dissection, abrasion or foreign body reaction. Adhesions produce consequences such as: infertility, intestinal obstruction, and pelvic-abdominal pain. The objective of this study is to evaluate the effects of Meloxicam, a selective cyclooxygenase-2 inhibitor, on the formation of postoperative peritoneal adhesions in an experimental animal model. Methods: Twenty female Wistar rats were submitted to laparotomy. Postoperative peritoneal adhesions were induced by scorching the serous surface of the colon. The animals were randomly divided into two experimental groups: one group received Meloxicam intramuscularly for 7 days, and the other served as a control group. They were sacrificed and evaluated at 15 days. Results: In the animals given Meloxicam, it was observed that a decrease in number (p = 0.018), severity (p = 0.004), extension (p = 0.011), density (p = 0.023), degree of inflammation (p = 0.002), vascular proliferation (p = 0.004) and fibrosis (p = 0.029) of adhesions, compared to the control group. Conclusion: In conclusion, this study demonstrated that the administration of Meloxicam intramuscularly significantly decreases the formation of postoperative peritoneal adhesions and, therefore, may be useful in their prevention. The effects of Meloxicam could not only be due to its anti-inflammatory action, but also to its effects on the expression of the Vascular Endothelial Growth Factor.